Gestalt approach and Psychopedagogy: a comprehensive look to the child-school totality - Dusi, Miriam Lúcia Herrera Masotti; Neves, Marisa Maria Brito da Justa; Antony, Sheila (Paidéia (Ribeirão Preto), 2006)
The following study aims to establish an interface between gestalt approach and Psychopedagogy. Gestaltpedagogy base theories are focused, its conception of holistic-relational field, the Contact Cycle theory and the contributions for the learning process and school practices comprehension. From Psychopedagogy, its conception, amplitude and processes evaluation and intervention for the child and educative institution are pointed out; the convergence of their theoretical and practical bases enclose the learning phenomenon, the psychopedagogy evaluation and intervention from a gestaltic standpoint. The interface seeks a new comprehension and interventionist action to the learning process and school complaints, to collaborate to the child development.